Renal Duplex Sonographic Evaluation of Type 2 Diabetic Patients. (1st June 2013) - Mancini, Marcello; Masulli, Maria; Liuzzi, Raffaele; Mainenti, Pier Paolo; Ragucci, Monica; Maurea, Simone; Riccardi, Gabriele; Vaccaro, Olga
Abstract : Objectives: The purpose of this study was to evaluate the renal volume and intrarenal hemodynamics with duplex sonography in a group of diabetic patients with normal renal function in comparison to nondiabetic controls. Methods: The renal volume and resistive index (RI) of segmental arteries were assessed by duplex sonography in 88 diabetic patients (44 male and 44 female; median age, 58 years [range, 37–69 years]) and 73 nondiabetic control participants (48 male and 25 female; median age, 53 years [range, 27–75 years]) without renal artery stenosis. Results: Both renal volume and RI values in the diabetic patients were significantly higher compared to the controls (mean volume ± SD: diabetic patients, 197.3 ± 47.6 mL; controls, 162.5 ± 35.2 mL; P < .0001; RI: diabetic patients, 0.70 ± 0.05; controls, 0.59 ± 0.06; P < .0001). Renal hypertrophy was present even in diabetic patients without proteinuria (renal volume: patients without proteinuria, 198.3 ± 45.9 mL; controls, 162.5 ± 35.2 mL; P < .005). Patients with higher RI values had significantly greater proteinuria (RI <0.75, 15.9 mg/g [range, 4.2–1718.9 mg/g]; RI >0.75, 37.9 mg/g [range, 11.34–2087.0 mg/g]; P < .02). Conclusions: Changes in renal volume and hemodynamics are detectable on sonography in diabetic patients. Those changes are also present in patients without proteinuria or signs of renal atherosclerosis and with both normal and increased glomerular filtration rates. These results indicate a potential role of duplex sonography in the early identification of morphologic and hemodynamic renal changes in type 2 diabetic patients.